An Alum-Free Jellyfish Treatment for Food Applications - Gianluca Bleve; Francesca Anna Ramires; Stefania De Domenico; Stefania De Domenico; Antonella Leone; Antonella Leone (Frontiers in Nutrition, 2021)
Jellyfish, marketed and consumed as food in The Far East, are traditionally processed using salt and alum mixtures. In recent years, the interest of Western consumers in jellyfish (JF) as a food source is increasing. In Europe [European Union (EU)], JF-derived food products are regulated by a novel food law, but methods for JF treatment and processing have not been developed yet. In this study, a protocol for the stabilization and processing of JF into semi-finished food products without the use of alum is proposed for the first time. Safety and quality parameters, together with a series of technological and nutritional traits, were used to monitor the proposed process and for the characterization of the JF-derived products. Calcium lactate (E327), calcium citrate (E333), and calcium acetate (E263), which are food thickening/stabilizing agents allowed by EU regulations, were used in order to control the presence of possible microbial pathogens and spoilage species. The use of calcium lactate and citrate led to an increase in texture values (~1.7–1.8-fold higher than in starting raw materials) and in several nutritional traits such as antioxidant activity, and protein and fatty acid content. In particular, the combination of JF treatments with calcium salts and phenolic compounds resulted in an antioxidant activity increase of up to 8-fold, protein concentration increase of up to 2.6-fold, fatty acid composition maintenance, and a ω6/ω3 ratio lower than 1. For the first time, the application of phenolic compounds to improve JF technological and nutritional features was verified. This study proposes a new procedure for JF treatment and stabilization useful for future potential food applications in Western countries.